Molecular technologies for detection of chemical and biological agents - Banoub, Joseph H.; Caprioli, R. M. (Springer, 2017)
This book describes the latest molecular insights needed to understand the chemical and biological (CB) agents and their associated biotechnologies. Its primary focus is to present and discuss molecular technologies such as mass spectrometry, chemical and biological sensors, chromatographic and electrophoretic separation, and comparisons of spectroscopic, immunological and molecular analyses of chemicals used for the detection of chemical and biological agents and to prevent terrorism. This NATO-ASI book also contributes to the critical assessment of existing knowledge on new and important detection technologies. It helps to identify directions for future research and to promote closer working relationships between scientists from different professional fields.
"Proceedings of the NATO Advanced Study Institute on Molecular Technologies for Detection of Chemical and Biological Agents, Calabria, Italy, 9-16 April, 2016."
Keywords: Chemical detectors -- Congresses.; Biosensors -- Congresses.; elektronické knihy; electronic books